Cardioprotective Effect of Acute Intradialytic Exercise: A Comprehensive Speckle-Tracking Echocardiography Analysis - Josse, Matthieu; Patrier, Laure; Isnard, Myriam; Turc-Baron, Cécile; Grandperrin, Antoine; Nottin, Stéphane; Mandigout, Stéphane; Cristol, Jean-Paul; Maufrais, Claire; Obert, Philippe (Journal of the American Society of Nephrology, 2023)
Hemodialysis (HD) can lead to acute left ventricular (LV) myocardial wall motion abnormalities (myocardial stunning) due to segmental hypoperfusion. Exercise during dialysis is associated with favorable effects on central hemodynamics and BP stability, factors considered in the etiology of HD-induced myocardial stunning. In a speckle-tracking echocardiography analysis, the authors explored effects of acute intradialytic exercise (IDE) on LV regional myocardial function in 60 patients undergoing HD. They found beneficial effects of IDE on LV longitudinal and circumferential function and on torsional mechanics, not accounted for by cardiac loading conditions or central hemodynamics. These findings support the implementation of IDE in people with ESKD, given that LV transient dysfunction imposed by repetitive HD may contribute to heart failure and increased risk of cardiac events in such patients. Hemodialysis (HD) induces left ventricular (LV) transient myocardial dysfunction. A complex interplay between linear deformations and torsional mechanics underlies LV myocardial performance. Although intradialytic exercise (IDE) induces favorable effects on central hemodynamics, its effect on myocardial mechanics has never been comprehensively documented. To evaluate the effects of IDE on LV myocardial mechanics, assessed by speckle-tracking echocardiography, we conducted a prospective, open-label, two-center randomized crossover trial. We enrolled 60 individuals with ESKD receiving HD, who were assigned to participate in two sessions performed in a randomized order: standard HD and HD incorporating 30 minutes of aerobic exercise (HDEX). We measured global longitudinal strain (GLS) at baseline (T0), 90 minutes after HD onset (T1), and 30 minutes before ending HD (T2). At T0 and T2, we also measured circumferential strain and twist, calculated as the net difference between apical and basal rotations. Central hemodynamic data (BP, cardiac output) also were collected. The decline in GLS observed during the HD procedure was attenuated in the HDEX sessions (estimated difference, -1.16%; 95% confidence interval [95% CI], -0.31 to -2.02; P = 0.008). Compared with HD, HDEX also demonstrated greater improvements from T0 to T2 in twist, an important component of LV myocardial function (estimated difference, 2.48°; 95% CI, 0.30 to 4.65; P = 0.02). Differences in changes from T0 to T2 for cardiac loading and intradialytic hemodynamics did not account for the beneficial effects of IDE on LV myocardial mechanics kinetics. IDE applied acutely during HD improves regional myocardial mechanics and might warrant consideration in the therapeutic approach for patients on HD.